Wage Setting in Multiproduct Firms - Jackie M.L. Chan; Michael Irlacher; Michael Koch; Luca Macedoni (CESifo GmbH, 2025)
This paper reveals a new determinant of wage markdowns at the firm level, namely, the product scope. Using matched employer-employee data on Danish manufacturing firms, we document a negative elasticity between wages and firm scope, which is of a similar magnitude but opposite sign as the firm-size wage premium. We rationalize the wage discount using a theory where workers value the opportunity to switch product lines as an amenity. Multiproduct firms exercise their monopsony power to offer lower wages. Our findings have important implications for understanding labor market dynamics in times of rising concentration from the contribution of large multiproduct firms.
Keywords: J31; J42; L25; D21; F10; 330; multiproduct firms; monopsony power; wages; amenities; labor share